Representasi keindahan bahasa dalam majma‘ al-bahrayn karya nasif al-yaziji: analisis stilistika terhadap estetika bahasa arab klasik - Caereny, Fajaricha Aurera (Maliki Interdisciplinary Journal, 2026)
This study aims to represent the beauty of language in Majma‘ al-Baḥrayn by Naṣīf al-Yāzijī through stylistic analysis. As an important figure in the revival of Arabic literature, Nasif al-Yāzijī revived the rhythmic prose style characteristic of the classical Arabic tradition by combining saj‘, wordplay, and figures of speech as the main aesthetic constructs. This study uses a qualitative-descriptive method with text analysis on the first page of the maqāmah, covering diction (al-lafẓ), saj‘, tarsī‘, figures of speech (tasybīh, isti‘ārah, kināyah), imagery, repetition, and parallelism. The results show the dominance of 10 classical Arabic diction, 7 saj‘, and 3 tarsī‘ patterns that form the rhythm and musicality of the text. Figures of speech are also prominent with 2 tasybīh, 3 isti‘ārah, and 2 kināyah that enrich the imagination and depth of meaning. In addition, there are 4 visual and motion images that emphasize the background atmosphere, accompanied by 5 forms of repetition and 3 parallelisms that strengthen the rhetorical aspect. Overall, these stylistic devices show that the beauty of al-Yāzijī's maqāmah is based on the density of language, structural play, and the power of images that present the narrative aesthetics typical of classical prose. This research confirms the role of Majma‘ al-Baḥrayn as a representation of the revival of classical language style as well as evidence of al-Yāzijī's creativity in strengthening the Arabic literary tradition through stylistic aesthetics.